The Economic Consequences of Family Policies: Lessons from a Century of Legislation in High-Income Countries - Claudia Olivetti; Barbara Petrongolo (Institute of Labor Economics (IZA), 2017)
We draw lessons from existing work and our own analysis on the effects of parental leave and other interventions aimed at aiding families. The outcomes of interest are female employment, gender gaps in earnings and fertility. We begin with a discussion of the historical introduction of family policies ever since the end of the nineteenth century and then turn to the details regarding family policies currently in effect across high-income nations. We sketch a framework concerning the effects of family policy to motivate our country- and micro-level evidence on the impact of family policies on gender outcomes. Most estimates of the impact of parental leave entitlement on female labor market outcomes range from negligible to weakly positive. The verdict is far more positive for the beneficial impact of spending on early education and childcare.
Keywords: J13; J16; J18; 330; parental leave; childcare; family policies; gender gaps